Review on the application of lexical chunks for English teaching in China / Shi Lijun, Tuan Sarifah Aini Syed Ahmad and Anealka Aziz Hussin - Shi, Lijun; Syed Ahmad, Tuan Sarifah Aini; Aziz Hussin, Anealka (Universiti Teknologi MARA Cawangan Kedah, 2023)
There are a variety of approaches to teach English in China. One of them is by using lexical chunks. The lexical approach has been believed to be an ideal way for English teaching and learning. In order to provide some insights on how lexical chunks has been used in English teaching in China, this article aimed to review the application of lexical chunks for English teaching in China by using the qualitative method. The instrument employed was the comprehensive literature review. Only 10 relevant research articles published since 2018 were selected from the Google Scholar using selected keywords. All the studies reported positive impacts on the application of lexical chunks in teaching English in China, but only two of them covered the attitude, and one was related to motivation. Therefore, more studies can be done with respect to attitude and motivation. Since the research on the application of lexical chunks in the teaching of English in China is limited, it is essential for future research to focus on this area especially on motivation. Studies could be also done in the future on different types of samples and using different instruments.